Transformasi Digital Dalam Akuntansi Manajemen: Tantangan Dan Peluang - Dea Meliana (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Digital transformation has become a major driver of change in management accounting, forcing companies to adapt to new technologies and change organizational culture. This study explores the challenges and opportunities faced by management accounting in the digital era. Key challenges include the integration of new technologies into existing systems, implementation costs, the need for new skills, data security, and changes in organizational culture. On the other hand, digital transformation offers significant opportunities, such as automation of accounting processes, real-time data access, in-depth data analytics, and increased data security through technologies such as blockchain. By leveraging digital technology, companies can improve operational efficiency, reduce costs, and increase competitiveness in the market. This study uses a literature study method with article analysis from academic databases to provide practical recommendations for accounting and management professionals in dealing with rapid and complex changes in today's business environment.